Negotiating the New Media Platforms: Youth and Political Images in Kenya - Lynete Lusike Mukhongo (tripleC: Communication, Capitalism & Critique, 2014)
New media platforms, particularly social networks act as vehicles for visual representation of a nation’s political discourse among the youth. Web 2.0 has created online spaces (private and public) that have been appropriated by Kenyan youth, locally, and in the Diaspora to weave their own political narratives and present them in forums that accommodate their views without fear of censorship or regulation that characterises “offline” communications. Using post structuralism, with emphasis on Roland Barthes “Death of the Author” and “Camera Lucida”, the article critically analyses how cultural values affect the interpretation of online political images from Kenya, by internet users from different culture zones. Further, the article discusses whether political images posted by the youth in Kenya on their online private spaces can be used to promote political stereotypes, subjectivities and perpetuate visual hegemonies; or whether it allows the youth to circumvent government surveillance tactics and afford nations an opportunity to correct the media hegemony by rewriting their own stories on a platform that is not just national, but transnational